HUBUNGAN ANTARA TINGKAT PENDIDIKAN, STATUS PEKERJAAN DAN TINGKAT PENDAPATAN DENGAN USIA PERKAWINAN PERTAMA WANITA DI KELURAHAN KOTALAMA KECAMATAN KEDUNGKANDANG KOTA MALANG - Lia Kurniawati; Siti Nurrochmah; Septa Katmawanti (Universitas Negeri Malang, 2016)
Abstract: The high age of first marriage of woman in Village Kotalama, especially in the age group <20 years old and the age group >30 years of having an effect on maternal and infant health cover, the risk of pregnancy, childbirth, infant and perinatal mortality circumstances. Therefore, the research entitled